EFFECT OF BREED AND DURATION OF EGG-STORAGE ON HATCHING AND SEVENTH-DAY PRODUCTION PERFORMANCE OF CHICKS - Jesuyon, O. M. A.; Adesina, H. O.; Adewumi, E. O.; Akinsola, K. L. (Nigerian Journal of Agriculture and Agricultural Technology, 2026)
Research was conducted to evaluate the effect of breed, pre-incubation storage duration and their interaction on day-old quality and 7th-day growth parameters of broiler chicks of Arbor acre and Ross 308 origins. A total number of 1200 eggs were collected in three (3) batches, and within each batch, eggs were randomly grouped and stored for 4, 7, and 10 days respectively before incubation. After hatching, birds within each batch/group were placed on a starter diet for seven days. The experiment design was factorial arrangement of breed (2) by storage days (3) in a completely randomized design (CRD). Data on chick quality and growth performance were collected from day-old to 7 days of life, and subjected to factorial ANOVA. Interaction of breed and egg-storage duration revealed the best navel quality and 7-day production efficiency in Arbor acre and Ross at 7- and 10-day pre-incubation egg-storage duration (P <0.050-0.001) respectively. Due to breed, Arbor acre presented better day-old chick activity and 7-day production efficiency than Ross 308 breed (P <0.050-0.001). The 7-day pre-incubation storage interval for hatching eggs produced the best day-old navel quality and 7-day production efficiency (P <0.050-0.001). Arbor acre and Ross eggs could be stored for 7 to 10-days pre-incubation, for best production performance at 7 days of age.